Preparação do compósito ferrita de níquel/nanotubos de carbono por micro-ondas para uso na reação de foto-fenton - Rigo, Caroline (2015)
In this study, the synthesis of the nickel ferrite composite/carbon nanotubes was accomplished through two different routes: conventional solvothermal method and solvothermal method assisted by microwave. The influence of the synthesis route into material's physical properties was investigated. Furthermore, the nickel ferrite, without carbon nanotubes presence, was synthesized by the solvothermal method assisted by microwave. The obtained materials were characterized by X-Ray Diffraction (XRD), Fourier Transform Infrared spectroscopy (FTIR), surface area and adsorption-desorption measurements by the Brunauer-Emmett-Teller method (BET), Differential Thermal Analysis (TGA) and Raman spectroscopy The materials produced were used as photo-Fenton catalysts for heterogeneous reactions, aiming the degradation of an organic dye (Acid Red 27) under the irradiation of visible light. The assays were performed in order to analyze the different process variables, citing pH, dye concentration, the mass of the catalyst and the hydrogen peroxide aliquot. The reactions rates constants were determined only for the material obtained through the route assisted by microwave, since the two composites present similar physical properties, and therefore we chose this composite , once the synthesis is performed in less time (30 minutes versus 20 hours the conventional method). The photo-Fenton reaction assays indicate that this composite has effective performance into degradation of organic pollutants in solution, with total color removal in 60 minutes of reaction for Acid Red dye concentration of 50 mg.L-1.